Pengaruh Faktor-Faktor Pproduksi Berbasis Konservasi Terhadap Hasil Minyak Nilam di Kecamatan Arongan Lambalek Kabupaten Aceh Barat - Agustiar Agustiar; Romano Romano; Muyassir Muyassir (Jurnal Manajemen Sumberdaya Lahan, 2015)
Abstract: Low productivity and quality of patchouli oil is partly due to the low genetic quality plants, cultivation technology which is still simple and not applying soil conservation techniques. This research is aimed to analyze the rate of using of production factor based on conservation through the result of patchouli oil in the Arongan Lambalek sub district Aceh Barat. The research are using survey method with production factors viewed consist of organic and un organic. The data analyzing used is double non linier regression with Cobb Dougglass function to analyze the production factors based on conservation through the result patchouli oil. The result of the research show that the production factors based on conservation is only the number of seed which has real influence through the result of patchouli oil (p 0,000), while the organic fertilizer, urea and SP 36 and KCL has no real influence. The using of the production factors based on conservation in patchouli oil agribusiness has been fulfill the principle of Increasing Return to Scale with the value is 1,358. Abstrak : Rendahnya produktivitas dan mutu minyak nilam antara lain disebabkan rendahnya mutu genetik tanman, tehnologi budidaya yang masih sederhana dan belum menerapkan tehnik konservasi lahan. Penelitian ini bertujuan untuk mengkaji tingkat penggunaan faktor produksi berbasis konservasi terhadap hasil minyak nilam di Kecamatan Arongan Lambalek Kabupaten Aceh Barat. Penelitian menggunakan metode survey dengan faktor-faktor produksi yang diamati terdiri dari organik dan anorganik. Analisis data digunakan Regresi Non Linier Berganda dengan fungsi Cobb Douglass untuk menguji faktor-faktor berbasis konservasi terhadap hasil minyak nilam. Hasil penelitian menunjukkan bahwa faktor-faktor produksi berbasis konservasi hanya jumlah bibit yang berpengaruh nyata terhadap hasil minyak nilam (p 0,000), sedangkan pupuk organik, urea dan SP 36 dan KCl berpengaruh tidak nyata. Penggunaan faktor-faktor produksi berbasis konservasi pada usahatani nilam, sudah memenuhi prinsip increasing return to scale dengan nilai 1,358